Moving mindsets: A multidimensional inquiry into urban justice through the lens of urban mobility and the evolution of public space - Davis, Saliegh (School of Architecture, Planning and Geomatics, 2024)
Moving Mindsets: A Multidimensional Inquiry into Urban Justice through the Lens of Urban Mobility and the Evolution of Public Space Inspired by my own experiences and driven by the transformative potential of transport systems, the focus of the dissertation is the revitalisation of the Pentech Metrorail Station, envisaging an integrated transport node that incorporates a vocational education centre and community information and resource centre. Emphasising the Cape Peninsula University of Technology's (CPUT) role and public realm vitality, the goal is to make the station a key node in the Belhar community, thereby nurturing vibrant and accessible public spaces that heighten the quality of life for all residents and users. The major routes linking the train station and the urban fabric are critically assessed and reconfigured to cater not only to the station but also to thoughtfully integrate public spaces and accommodate the evolving needs of the local populace with the ambition of enabling the residents to explore their city through improved movement routes. The public spaces are designed as platforms to promote social cohesion, community identity and facilitate academic interaction. The theoretical investigation of the project delves into the profound influence of architectural and urban design on social behaviour particularly in respect to how users interact in public spaces. These relationships are investigated in order to create an architectural design that responds effectively to present conditions and simultaneously emerges as an important landmark in Belhar and a template for future developments in the area in alignment with the Metropolitan Spatial Development Framework's (MSDF) proposed North-South link.